Printed UWB Antenna with Coupled Slotted Element for Notch-Frequency Function - X. L. Bao; M. J. Ammann (International Journal of Antennas and Propagation)
A novel printed monopole antenna employing a slotted-plate, which is electromagnetically coupled to the microstrip-fed planar element, is proposed to provide notch-frequency function. This technique enables stopband characteristics with improved control, compared to placing the slot in the microstrip-fed element. A detailed investigation of the rejectband properties has been made for the UWB antenna. Measured data for the optimized case show the 10 dB return loss bandwidth to be 9.8 GHz (from 2.80 GHz to 12.60 GHz) with a notchband frequency from 5.15 GHz to 5.825 GHz. Propagation measurements indicate that the electromagnetically coupled slot provides a greater reduction in stopband gain for the three principal planes, compared to placing the slot in the fed element. This is desirable to mitigate interference from WLAN systems. A full parametric study of the antenna is presented.